MEMBANGUN RANTAI PEMBELIAN ULANG WISATAWAN - Setiaji, Yudi (Sekolah Tinggi Pariwisata AMPTA, 2012)
Satisfaction and rebuying become the key factor influencing advantage and growth of tourism company on a long term. This research test the model of relation of quality perception, satisfaction, and rebuying tourist market which a mediated by trust. Quesioner used to collect the data from 300 respondent, test the validity and reliability confirmation with the coefficient of cronbach alpha. Analyse the data to test the hypothesis this research used a structural equation model ealthily to collect the data. Result of empirical study indicate that a whole found a causality relation at four accurate a company, satisfaction directly influenced by perception of quality and rebuying mediated by trust of cutomer to company. This research implication indicate that the company owning higher level tourist satisfaction storey; level will be more easy to cutomer become the devoted to do the rebuying, therefore strengthen the ability and improve its specialty go together the cutomer service, will make the company do not only limited to able to hold out attacked from serangan competitor but also able to grow ealthily industrial market service which hyper competition. Keywords: rebuying-quality-satisfaction change, trust, and structural equation model.